Inhibitive Properties of Anredera Cordifolia Extract on Escherichia Coli Swimming Motility - Alexander Tobias Kristanto; Maria Silvia Merry; Suryani Hutomo (Faculty of Medicine Universitas Kristen Duta Wacana, 2021)
Background Escherichia coli, a Gram-negative bacterium, is one of the main etiology of urinary tract infection (UTI). An important pathogenicity factor influencing biofilm production is its motility, swimming, or swarming. Anredera cordifolia (AC) leaves have been proven to have an antibacterial effect on various Gram-positive and Gram-negative bacteria, including E. coli.Objective To determine the effect of AC leaves extract on swimming motility property of E. coli derived from UTI patients. Methods AC leaves were extracted with the maceration method. E. coli was identified and isolated from UTI patients. There are4 diluting concentrations of AC leaves extract (from 875 mg per ml to 7000 mg per ml) and one negative control. The preparation underwent incubation, inoculation, and re-incubation. Swimming motility was measured manually, and the result was tested for significant difference between each dose with one-way ANOVA (limit of significance is 0.05)Results On AC leaves extract concentration of 1750 mg per ml, the swimming motility has been inhibited significantly compared to negative control and lower concentration of 875 mg per ml (0.543 cm vs 1.673 cm and 1.358 cm, respectively; p < 0.001). Increasing concentration (3500 mg per ml and 7000 mg per ml) did not show a significant difference in inhibition compared to 1750 mg per ml (0.539 cm and 0.530 vs 0.543).Conclusion AC leaves extract with a concentration of at least 1750 mg per ml would inhibit the swimming motility of E. Coli derived from UTI patients.